2018
DOI: 10.1002/fee.1949
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient retention during ecosystem succession: a revised conceptual model

Abstract: We propose an important revision to a previously published conceptual model of nutrient retention during terrestrial ecosystem succession, which predicted that ecosystem losses of limiting nutrients such as nitrogen (N) should increase as rates of biomass accumulation slow during late stages of succession. This revision explicitly recognizes that mineral soil horizons (the layers of subsoil beneath the organic‐rich surface layers) can behave as an “N bank”, serving as a source of N for growing forests early in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…A study conducted in Hubbard Brook Experimental Forest also reported similar results, with temporarily high N leaching during initial stage of forest regeneration (Valipour et al 2018). The tree N uptake exceeded the net N mineralization when N leaching was the lowest (Figure 3(a,b)), reflecting the role of tree N uptake in controlling ecosystem N losses (Vitousek and Reiners 1975;Lovett et al 2018).…”
Section: N Cycle Processes and N Stockssupporting
confidence: 54%
See 1 more Smart Citation
“…A study conducted in Hubbard Brook Experimental Forest also reported similar results, with temporarily high N leaching during initial stage of forest regeneration (Valipour et al 2018). The tree N uptake exceeded the net N mineralization when N leaching was the lowest (Figure 3(a,b)), reflecting the role of tree N uptake in controlling ecosystem N losses (Vitousek and Reiners 1975;Lovett et al 2018).…”
Section: N Cycle Processes and N Stockssupporting
confidence: 54%
“…However, on the contrary, the N leaching decreased from 3.25 to 3.05 kg N ha À1 yr À1 , following a change in N deposition from 40% to 60%. This might be due to an assumption of the FBDCAN model, that the tree N uptake occurs before N leaching (Vitousek and Reiners 1975;Lovett et al 2018). This resulted in a decrease in N leaching, even though the N deposition increased.…”
Section: Verificationmentioning
confidence: 99%
“…At Cary Institute for Ecosystem Studies in the Catskills Mountains, NY (abbreviated NY1), 100 kg N ha −1 year −1 was applied to treatment plots from 1996 to 1999, and then 50 kg N ha −1 year −1 was applied from 2000 to 2006, as granular NH 4 NO 3 four times per year (Lovett & Goodale, 2011). We anticipated the effects of fertilizer treatments at NY1 would be detectable in our samples because, although treatments ceased in 2006, fertilizer N applied in hardwood forests can be retained in soil for decades (Lovett & Goodale, 2011; Lovett et al., 2018). At the Soil Warming × Nitrogen Addition Study at the Harvard Forest Long Term Ecological Research site (MA), fertilization treatments began in 2006 and are ongoing.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been widely used to assess terrestrial elemental balance in non-permafrost ecosystems, generating fundamental insights into ecosystem succession and other processes over time (Fisher et al, 1998;Lovett et al, 2018;McClelland et al, 2007;Vitousek & Reiners, 1975). In high-latitude locations, this approach has been limited to a small number of watersheds (Kling & Kipphut, 2000;Malone et al, 2018;Metcalfe et al, 2018;Parham et al, 2013;Temnerud & Bishop, 2005), largely due to logistical limitations (but see Shogren et al, 2019).…”
mentioning
confidence: 99%